Journey of SARS-CoV-19 from Mucosa Towards Angiotensin-Converting Enzyme2 Pathway: A Review - Singh, Preeti; Adhikari, Biplob (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
The disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) or simply corona virus disease-2019 (COVID-19), has rapidly spread throughout the world. World Health Organization declared a global health emergency on January 30, 2020 announcing it as a Pandemic. The outbreak of the disease has posed serious health threat. A search was conducted for review which included various articles from 2019 to 2021 in PubMed/MEDLINE with keywords ACE2, 2019 NCOV, pandemic, physiopathology, SARS, Transmission. Both humoral and acquired immunity are targeted by the virus during progression of diseases. A cellular biology perceptive of pathogenesis is useful forframing clinical course of the diseases and its related complication. Knowledge of underlying pathophysiology regarding release of innate immune modulators such as CXCL10, beta and alpha interferons will facilitate the development of therapeutic modalities in future. Despite implementing all the preventive efforts SARS-CoV-2, exponential mode of infection rate is still existing with epidemic doubling time less than a week. In this review, an update on pathophysiology, cell biology of virus and immune modulation related to diseases are considered and has been described. Any of the mechanisms and assumptions discussed in the article and in our understanding of SARS-CoV-2 may be revised as further evidence emerges.